Evaluasi Kapabilitas Keamanan Teknologi Informasi pada Proses APO13 dan DSS05 berdasarkan Framework Cobit 5 (Studi pada Dinas Komunikasi dan Informatika Kota Malang) - Muhammad Fariz Arizali Effendi; Andi Reza Perdanakusuma; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Dinas Komunikasi dan Informatika (DISKOMINFO) is a government agency which provide IT services to local government (in this case Malang City Government). Utilization of IT functions is based on the principles of confidentiality, integrity and availability. The existence of the Industrial Revolution 4.0 era requires government authorities to increase the vigilance of managing IT security so that security potential is handled and to improve performance efficiency. Thereby measuring the quality of IT security management to ensure information technology is applied in accordance with organizational strategies. Measurement of IT security capabilities at DISKOMINFO Malang City is done by comparing the conditions of IT security management that have been achieved with the conditions desired by the agency. This study uses a qualitative method based on COBIT 5 guidelines focusing on the APO13 (Manage Security) and DSS05 (Manage Security Services) processes. Data collection is done by observation, use of COBIT 5 assessment sheet instruments, checklist sheets, and direct interviews. Based on the research results, the results obtained in the APO13 (Manage Security) process reached level 1 (Established Process), while the DSS05 (Manage Security Services) process reached level 0 (Incomplete Process). DISKOMINFO Malang City hopes that both processes can reach level 2 (Managed Process). So that there is a gap of one level in the APO13 process and two levels in the DSS05 process. There are 13 recommendations in the APO13 process and 15 recommendations in the DSS05 process. Then the improvement roadmaps are presented to DISKOMINFO Malang City to achieve the target level.